Iatrogenic dry eye disease: An eledoisin/carnitine and osmolyte drops study - Nebbioso, Marcella; Evangelista, Mariasilvia; Librando, Aloisa; Plateroti, Andrea Maria; Pescosolido, Nicola (Biomedicine & pharmacotherapy, 2013)
To evaluate the effects of an eye drop containing eledoisin and carnitine in patients suffering from primary open-angle glaucoma (POAG) and ocular discomfort syndrome secondary to a chronically treated with eye drops containing benzalkonium chloride (BAK) as preservative. The dry eye disease was defined as a multifactorial drop disease concerning tears and ocular surface, which brings to discomfort symptoms and visual disorders with potential damage to the ocular surface. Several studies underlined the beneficial effects of secretagogues drugs, such as eledoisin. It is a neuro-peptide extracted from the salivary glands of some shellfishes. Recently, it has been also showed the protective role of carnitine in respect of the ocular surface exposed to the tear film hyperosmolarity. This randomized double-blind pilot study has been evaluated by lubricant eye drop solutions containing eledoisin and carnitine in 40 patients with ocular discomfort syndrome secondary to POAG, since that the patients were chronically treated with eye drops which decrease eye pressure and contain BAK as preservative. The subjects filled out a questions form concerning the severity of the symptoms and their impact on daily activities. Subsequently Fluorescein Breakup Time (FBUT), Schirmer Test 1 (ST), and Ocular Protection Index (OPI) were measured at baseline and after 15days of treatment. At the end of therapy it was possible to match the beneficial effects of eye drops with carnitin, taurine, sodium hyaluronate and eledoisin. In fact, after 15days of treatment, patients of group 1 showed a decrease of approximately 50% concerning the severity of symptoms and a significant improvement of the tests valued. In summary, lubricant eye drops that restore physiological hosmolarity and stimulate tear production represent a promising strategy for dry eye syndrome.